PENGARUH KEPEMIMPINAN TERHADAP TINGKAT STRESS DAN KOMITMEN KERJA PERSONIL MAKO KOARMADA I TNI ANGKATAN LAUT - Sigit Dandung Utomo; Ermaya Suradinata; Sampara Lukman; Ika Sartika (GoAcademica Research dan Publishing, 2020)
According to data sourced from Koarmada I TNI AL, during 2015 to 2019, the average mental pressure sufferer on Indonesian Navy personnel grew by around 5.19% per year. From the search results of the Indonesian Navy archives, mental stress sufferers are generally caused by internal family, economic problems, difficulty in adapting, to leadership problems in the unit which are deemed not accommodating the aspirations of the personnel concerned. Therefore, this study focuses on analyzing the influence of leadership on the level of stress and work commitment of the Indonesian Navy's Mako Koarmada I personnel. This research uses quantitative methods. The quantitative approach itself uses the estimation technique of Structural Equation Modeling (SEM) and a literature review to explain the quantitative findings of this study. This study uses data sourced from 324 respondents. The results of this study indicate that the leadership variable has a significant effect on reducing stress levels, increasing work commitment, and increasing the social welfare of the personnel of Mako Koarmada I TNI AL. The success of this leadership commitment can occur in the long term and sustainably if the basis is oriented towards the development of the quality of human and organizational resources or what is known as transformative leadership as a new concept in this dissertation.